Appreciating Islamic contemporary art of Afghanistan country / Nurul Syazlina Che Yusof...[et.al] - Che Yusof, Nurul Syazlina; Mohamed Saat, Nor Kamalia; Md Zain, Dzul Haimi; Mokhtar, Mumtaz (2016)
One observation study done by looking at contemporary Islamic art in Afghanistan in the manifestation of tawhid. There has been some research done on the contemporary art of Afghanistan after the effect of war. The main purpose in this study is to establish the manifestation of tawhid in the artworks in Afghanistan. Four selected Afghanistan artists: Lida Abdul, Rada Akhbar, Mokhsin Wahidi and Malina Sulaiman will be analyzed from the aspect of axiology, ontology, psychology, epistemology and logic in the artworks. The method of analysis will be based from Feldman theory of art. This study shows that the themes of these artists are still about destruction and the impact of war. Nevertheless, their cultural elements are still maintained, in their artworks as well as their attempts to manifest the concept of tawhid.